(untitled) (Economics and region, 2020)
The paper justifies the priorities of the brand differentiation strategy in the mineral water market taking into account the market specifics. The structural elements of the differential strategy are singled out for the domestic mineral water brands. The prospects of further market analysis of the mineral water market are determined.